LEGAL TRUTH: THE CONFLICT BETWEEN REAL JUSTICE AND LEGAL JUSTICE (The Pretoria Student Law Review, 2021)
The following article is a chapter taken from my dissertation, and as such needs to be situated for the reader. The dissertation is a philosophical discussion concerning the divergence between ‘legal truth’ and ‘factual truth’, practically illustrated by critically evaluating the effect that our law of evidence, criminal procedure as entrenched in the Criminal Procedure Act, and the evidentiary exclusion clause entrenched in section 35(5) of the South African Constitution have on the ultimate decision of the court. It argues that often these rules and procedures obscure the truth rather than assist in finding it. The crux of the discussion revolves around decisions of our criminal courts, where accused persons who are factually guilty are acquitted due to the operation of our evidence rules and procedures which call for the exclusion of evidence in specific instances or on technical grounds. The result of this exclusion is that relevant reliable evidence is deemed not to exist for the purposes of the trial, and evidence which might otherwise have lead to the conviction of the accused person is put beyond the reach of the courts. This article then deals specifically with the debate surrounding ‘what is justice?’; it looks at various concepts of justice and seeks to show that within the confines of our positivistic criminal justice system — a marriage between positive and natural law approaches — we might well be able to avoid decisions that are ‘legally correct’ yet offend one, as one cannot really say that justice was served.
Keywords: ‘legal truth’; ‘factual truth’; law of evidence; criminal procedure; Criminal Procedure Act; ‘what is justice?’; positive law